Teaching and learning in Japan (Cambridge University Press, 1996)
This text provides an in-depth examination of Japanese learning and teaching in many contexts across the life span of the Japanese people. Contemporary Psychology "Teaching and Learning in Japan resonates within the scholarly tradition of Robert Bellah's landmark study of the relationship of Japanese religion to the everyday lives of people in the Tokugawa period".